STRATEGI KARANG TARUNA DALAM MENINGKATKAN PARTISIPASI SOSIAL PEMUDA DI KELURAHAN TIMBANGAN KABUPATEN OGAN ILIR - Riska Wulandari; Henny Helmi; Shomedran; Azizah Husin (STKIP Subang, 2026)
This study aims to analyze the strategies of Karang Taruna in increasing youth social participation in Timbangan Village, Ogan Ilir Regency, which is motivated by the low level of youth involvement in social community activities. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The focus of the study is on organizational strategies including planning, implementation, and evaluation of activities. The results show that the strategies implemented have not been optimal due to the lack of program innovation, weak organizational communication, and low youth involvement in activities. Therefore, it is necessary to strengthen strategies through the development of more engaging programs, improved communication, and active member involvement in order to increase youth social participation optimally and sustainably